The "Chinese Confucian" and the "Chinese Buddhist" in British Burma, 1881-1947 - Hooker, Michael B. (Journal of Southeast Asian studies, 1990)
In 1893 the British introduced a comprehensive legal system in Burma. The guiding principle of the judicial and legislative system was that each racial or religious group had the right to its own law in matters of religion and custom. However, one group, the "Chinese Confucian" escaped the legislation and in the period 1881-1947 caused the courts some considerable problems. The paper deals with the problems of Chinese Confucians and the nature of Buddhism and Confucianism. (DÜI-Sen)